2016
DOI: 10.1007/s10661-016-5383-3
|View full text |Cite
|
Sign up to set email alerts
|

Current status of seawater quality in Digha (India), northwestern coast of the Bay of Bengal

Abstract: The present investigation was intended to assess the seawater quality of Digha (India) in the northwestern coast of the Bay of Bengal. Digha is a meso-tidal coastal plain located between two major estuarine systems, i.e. Subarnarekha and Hooghly located respectively on the western and eastern sides of the West Bengal along the northeast coast of India. The sampling was made at nine stations at various distances. Significant seasonal variations in environmental parameters and nutrients were observed during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Species richness positively correlates with the DO that is why species richness is higher during monsoon and post monsoon season among all the season. Species richness also fluctuates on the study sites depending on the DO, site Digha is the most affected one in case of species most of the time associated with tourist seasons (Roy ; Pitchaikani, Kadharsha et al 2016; Roy and Shamim 2020). While being the major fish landing centers; Digha-mohana and Shankarpur show more species richness ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species richness positively correlates with the DO that is why species richness is higher during monsoon and post monsoon season among all the season. Species richness also fluctuates on the study sites depending on the DO, site Digha is the most affected one in case of species most of the time associated with tourist seasons (Roy ; Pitchaikani, Kadharsha et al 2016; Roy and Shamim 2020). While being the major fish landing centers; Digha-mohana and Shankarpur show more species richness ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Turbidity of the sea water depends on various factors including eutrophication, sedimentary runoff, dissolved colored organic matter along with high number of phytoplankton (Pitchaikani, Kadharsha et al 2016). Even though turbidity sometimes may affect the fish diversity and species richness (mostly in the sea water where greater portion of coral reefs are present), our study sites have shown positive relationship with turbidity.…”
Section: Resultsmentioning
confidence: 99%
“…According to Pitchaikani et al 22 , the coastal aquifer in West Bengal is facing nitrate problems, which leads to heath-related issues in the populations of that region. In this coastal region, few researchers gave attention to determining the nitrate concentration and its effect on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this point of view, a detail study on coastal sand of Digha region (which is in eastern coast of India) [19] has been selected for this present study. Digha is situated between the coastal tract of adjacent Bay of Bengal and the boarder of two states: West Bengal and Orissa [19,28,31]. Moreover this area lies within the seismic zone III [7].…”
Section: Introductionmentioning
confidence: 99%